Vitamin D Supplementation Improves Uterine Receptivity in a Rat Model of Vitamin D Deficiency: A Possible Role of HOXA-10/FKBP52 Axis - Ashour, Hend; Gamal, Sara Mahmoud; Sadek, Nermeen Bakr; Rashed, Laila Ahmed; Hussein, Rania Elsayed; Kamar, Samaa Samir; Ateyya, Hayam; Mehesen, Marwa Nagi; ShamsEldeen, Asmaa Mohammed (Frontiers in Physiology, 2021)
Synchronized uterine receptivity with the time of implantation is crucial for pregnancy continuity. Vitamin D (VD) deficiency has been linked to failure of implantation. Therefore, we tested the link between the Homeobox transcription factor-10/immunophilin FK506-binding protein 52 (HOXA-10/FKBP52) axis and the uterine receptivity in VD deficient rats. The effect of VD supplementation at different doses was also investigated. 48 pregnant rats were divided into 6 groups (8/group); normal control rats fed with standard chow (Control), control rats supplemented with VD (equivalent dose to 400 IU/day) (Control-D400). VD deficient group (DEF) and three VD deficiency groups with VD supplementation equivalent to 400, 4000, and 10,000 IU/day (DEF-D400, DEF-D4000, DEF-D10.000 respectively). The expression levels of HOXA-10/ FKBP52, progesterone level, histological evaluation of decidualization using osteopontin (OSN) and progesterone receptor (PGR) were estimated. Assessment of uterine contractility was conducted for all rats. The study showed downregulation of HOXA-10/FKBP52 together with increased amplitude and frequency of uterine contractility in DEF group compared to control. VD dose –dependent supplementation restored progesterone/receptor competency, upregulated the expressional response of HOXA-10 and its downstream FKBP52, improved uterine receptivity and endometrial decidualization at the time of implantation that was documented by increased area % of OSN and number of implantation beads.